Basal cell carcinoma: A 6-year clinicopathological study from the Sub-Himalayan Region of North India - Rashmi Kaul Raina; Vikram K Mahajan; Tashi Dolma Bodh; Bal Chander; Suman S Chandel; Karaninder S Mehta (Wolters Kluwer Medknow Publications, 2019)
Background: Basal cell carcinoma (BCC) has not been studied in the population of the Sub-Himalayan region in the North India, as it has been done in the rest of India. This study was performed to analyze the clinicopathological spectrum of BCC in this population. Materials and Methods: The present study is a hospital-based open-cohort observational study which was carried out in the Departments of Pathology and Dermatology at a tertiary care center of Himachal Pradesh, India, from January 2012 to December 2017. All the patients with the histopathological diagnosis of BCC were included in this study. Results: Of the 46 cases of BCC analyzed during the 6-year study period, 30 (65.3%) cases were female and 16 (34.7%) cases were male. The mean age was 65.7 ± 12.9 years and 31.4% (14/46) were in the 61-70 years age group. Majority of the lesions were located in the head-and-neck area and the nose was the most common site. The most common histological type was the solid variant. Conclusion: This study highlights that BCC is not rare in Indians and is more common in females in this region. This study also reveals the frequency of clinicopathological patterns of BCC in this region.